Experiences with image quality and radiation dose of cone beam computed tomography (CBCT) and multidetector computed tomography (MDCT) in pediatric extremity trauma - Tschauner, Sebastian (Skeletal Radiol, 2020)
INTRODUCTION: Novel dedicated extremity cone beam computed tomography (CBCT) devices, recently introduced to the market, raised attention as a possible alternative in advanced diagnostic pediatric trauma imaging, today usually performed by multidetector computed tomography (MDCT). This work aimed to compare image quality and radiation dose of CBCT and MDCT. MATERIALS AND METHODS: Fifty-four CBCT-MDCT examination pairs, containing nine MDCTs acquired in parallel prospectively and 45 MDCTs matched in retrospect, were included in this study. Image quality was analyzed semi-objectively by measuring noise, contrast-to-noise ratio (CNR), and signal-to-noise ratios (SNR) and subjectively by performing image impression ratings. CT dose records were readout. RESULTS: Image noise was significantly lower in CBCT compared with MDCT, both semi-objectively and subjectively (both p < 0.001). CNR and SNRs were also in favor of CBCT, though CBCT examinations exhibited significantly more beam hardening artifacts that diminished the advantages of the superior semi-objective image quality. These artifacts were believed to occur more often in children due to numerous bone-cartilage transitions in open growth plates and may have led to a better subjective diagnostic certainty rating (p = 0.001). Motion artifacts were infrequently, but exclusively observed in CBCT. CT dose index (CTDI(vol)) was substantially lower in CBCT (p < 0.001). CONCLUSION: Dedicated extremity CBCT could be an alternative low-dose modality in the diagnostic pathway of pediatric fractures. At lower doses compared with MDCT and commonly affected by beam hardening artifacts, semi-objective CBCT image quality parameters were generally better than in MDCT. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00256-020-03506-9) contains supplementary material, which is available to authorized users.